2022
DOI: 10.3390/antiox11091803
|View full text |Cite
|
Sign up to set email alerts
|

Carob Extract Supplementation Together with Caloric Restriction and Aerobic Training Accelerates the Recovery of Cardiometabolic Health in Mice with Metabolic Syndrome

Abstract: Carob, the fruit of Ceratonia siliqua L. exerts antidiabetic, anti-inflammatory, and antioxidant effects and could be a useful strategy for the treatment and/or prevention of metabolic syndrome (MetS). The aim of this study was to analyze whether supplementation with a carob fruit extract (CSAT+®), alone or in combination with aerobic training, accelerates the recovery of cardiometabolic health in mice with MetS subjected to a caloric restriction. For this purpose, mice were fed with a high fat (58% kcal from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…C. siliqua pods are known for their antioxidant properties that are of value for the amelioration and prevention of many disorders [ 33 , 34 ]. In the literature, there are many studies comparing different extraction methods to prepare an active extract.…”
Section: Discussionmentioning
confidence: 99%
“…C. siliqua pods are known for their antioxidant properties that are of value for the amelioration and prevention of many disorders [ 33 , 34 ]. In the literature, there are many studies comparing different extraction methods to prepare an active extract.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study suggest that rats fed a high-fat diet and treated with carob pulp extract had significantly lower weight gain compared to the untreated rats. The possible mechanisms for this phenomenon are numerous and include the inhibition of adipocyte proliferation and differentiation [31], reduction of food intake [32], decline in body glucose and lipid content [36], increase in serum adiponectin [27,30], decrease in leptin resistance [33,37,38], and inhibition of fat accumulation in the liver [31]. Our study addresses two of these mechanisms.…”
Section: Effects On Obesitymentioning
confidence: 96%
“…Several studies on animal models have reported the impact of carob on body weight and proposed various explanatory mechanisms [31,32,36]. Fujita et al [31] showed that supplementation with carob pod polyphenols (CPPs) significantly decreased body weight gain in high-fat-fed mice.…”
Section: Effects On Obesitymentioning
confidence: 99%
See 2 more Smart Citations